The agent-based Solow growth model with endogenous business cycles - Ulrich Stolzenburg (Kiel University, Department of Economics, 2015)
This article describes a simulated monetary macro model with different types of interacting agents. As such, it is assigned to the field of agent-based computational economics (ACE), where agents become virtual objects in a computer simulation. The ACE model core with labor market and goods market interaction between households and firms is adopted from Lengnick (2013), whereas production technology and technological progress of firms are adopted from the neoclassical Solow (1956) model. Nominal interest rates are set in accordance with the Taylor (1993) principle, characterized by strong responses of monetary policy to deviations from inflation target. Although inflation desirably follows lagged output in a pro-cyclical manner, the dynamic system allows for long-run stability of inflation rates. Firms on aggregate level endogenously generate waves of higher and lower investment. A recurrent cyclical movement of aggregate economic activity, in particular demand, employment and inflation, is transmitted from these waves of investment activity. Cyclical patterns of boom and bust emerge with a frequency of approximately seven years just like Juglar-type cycles. Moreover, the model generates a short-run Phillips-curve relationship, long-run neutrality of monetary policy and business cycle patterns similar to the Goodwin (1967) model. Fiscal stabilization policy is shown to dampen macroeconomic fluctuations, thus allowing for a higher level of average employment. Calibration of model parameters is conducted to generate realistic orders of magnitude of important macroeconomic proportions. The newly developed model is a combination of ideas from different economic perspectives and contributes to macroeconomic model-building under the paradigm of agent-based computational economics.
Keywords: 330; Agent-Based Computational Economics; Demand-Led Economic Growth; Solow-Swan; Monetary Policy; Phillips Curve; Stabilization Policy